Length-frequency distribution, length-weight relationship and condition factor of sompat Grunt Pomadasys jubelini (Cuvier, 1830) off Lagos Coast, Nigeria - Adebiyi, Fatimat Adenike (Universiti Putra Malaysia Press, 2013)
Length-frequency distribution, length-weight relationship and condition factor of sompat grunt Pomadasys jubelini off the Lagos coast, Nigeria were investigated in order to study the growth pattern of P. jubelini. A total of four hundred and fifty specimens of P. jubelini were used for this study with body lengths ranging from 13.9-26.6cm (total length) and 11.2-22.1cm (standard length). The body weight ranged from 26.8g to 175.1g. The length-frequency distribution revealed high abundance of P. jubelini in the 21.0-21.9cm (total length) size group which accounted for 17.8% of the total specimens examined. The length-frequency distribution showed a poly-modal size distribution. Length-weight relationship was determined by the regression equation Log W = -1.5325 + 2.8177 Log L (n= 450, r2= 0.69, p < 0.05). P. jubelini showed negative allometric growth (b = 2.8177) which indicated proportionate growth was more in body length than in body weight. The mean condition factor was significantly higher for males (1.92 Â± 0.02) as compared to females (1.75 Â± 0.03) (p < 0.05). Results of this study are important and relevant for the stock assessment and fishery management of P. jubelini in the Lagos coast.